2015
DOI: 10.1055/s-0035-1564837
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of the Hemostatic System in Polycystic Ovarian Syndrome

Abstract: Polycystic ovarian syndrome (PCOS) affects 12 to 19% of women and has reproductive and metabolic features (endothelial dysfunction, increased diabetes, and cardiovascular risk factors). It also appears to have altered coagulation and fibrinolysis with a prothrombotic state with epidemiological evidence of increased venous thromboembolism. We aimed to comprehensively assess hemostasis in women with PCOS versus control women. In an established case-control cohort of lean, overweight, and obese women with (n = 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
(94 reference statements)
1
15
1
Order By: Relevance
“…Moreover, high thrombin generation is associated with first and recurrent VTE and possibly with coronary atherosclerosis (13, 14, 15). Thrombin generation has been found to be elevated in PCOS (12), but conflicting data exist (16). In a previous study, our group found high thrombin generation, PAI-1 and hsCRP to be linked to the overweight and insulin-resistant PCOS phenotype (17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high thrombin generation is associated with first and recurrent VTE and possibly with coronary atherosclerosis (13, 14, 15). Thrombin generation has been found to be elevated in PCOS (12), but conflicting data exist (16). In a previous study, our group found high thrombin generation, PAI-1 and hsCRP to be linked to the overweight and insulin-resistant PCOS phenotype (17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…Oral contraceptive pills may increase cardiovascular disease and increase the risk of venous thromboembolism [3,119] . A recent study by Burchall et al [120] reported impaired fibrinolysis (elevated plasminogen activator inhibitor-1 and plasminogen) in women with PCOS versus controls, even after adjustment for age and BMI. This was exacerbated by oral contraceptive pill treatment.…”
Section: Hyperandrogenismmentioning
confidence: 96%
“…Women with PCOS have a significantly higher risk of venous thromboembolism compared with non-affected women [119] . These risks are exacerbated by oral contraceptive pill use, a common PCOS management strategy, targeting reproductive features including menstrual cycle regulation and hirsutism [120] . Oral contraceptive pills may increase cardiovascular disease and increase the risk of venous thromboembolism [3,119] .…”
Section: Hyperandrogenismmentioning
confidence: 99%
“…Some possible reasons for increased plasma fibrinogen are: increased inflammatory processes [64], decreased fibrinolysis [65], and as an acute phase reactant. Enhancement in fibrinogen level stimulates RBC aggregation and significantly increased resistance in blood flow [66].…”
Section: Metabolic Disorders and Pcomentioning
confidence: 99%